How do Clinicians Use Electronic Health Records for Respiratory Support Decisions? A Qualitative Study in Critical Care - Tianyi Zhang; Jarrod Mosier; Vignesh Subbian (ACI Open)
Objectives Selecting appropriate respiratory support in critical care is complex, and some decisions require information that may be unknown when the treatment assignment is necessary. Digital technologies such as electronic health records (EHR) are essential components in critical care medicine to support respiratory support care delivery and management of patients with respiratory failure. However, there are limited studies on EHR use that enable clinical decisions related to respiratory support. The objective of this study is to understand how clinicians use EHRs for their decision-making related to respiratory support in intensive care units (ICUs).